(untitled) (Research, Society and Development, 2025)
The aim was to quantify nitrite in sausages sold in bulk, identify the microorganisms present and associate their development with the concentration of nitrite. The 15 bulk sausage samples were analyzed to identify microorganisms on the surface of the sausages and to quantify nitrite. Microbiological analyses were carried out for Salmonella spp, Escherichia coli, Staphylococcus aureus and molds and yeasts, using culture media such as pre-enrichment (non-selective), enrichment (selective) and fermentation broths and solid media. Nitrite quantification was carried out in two stages, starting with the extraction of nitrite from the crushed samples followed by quantification by spectrophotometry (540 nm) and the nitrite standard curve was used for the calculation. The results showed the absence of E. coli and fecal coliforms, and the presence of Samonella sp in all the samples, about 6.7% contained S. aureus, 33.3% total coliforms and 53.3% molds and yeasts. Nitrite was calculated using the straight line equation (y= 0.7574x + 0.0046) and the lowest concentration was 0.62 ± 0.32 mg/kg-1 and the highest was 1.77 ± 0.09 mg/kg-1, which is below the maximum limit allowed by health legislation (150 mg/kg-1). The presence of pathogenic bacteria may be related to poor personal hygiene practices, improper handling, inappropriate packaging and storage, so the comparison between the presence of microorganisms and nitrite was inconclusive. Vacuum repackaging could be an alternative for controlling microbial development, as it reduces handling and cross-contamination.